Literasi Membaca dan Menulis Dalam Mencegah Perundugan Pada Mahasiswa Kedokteran Universitas Negeri Gorontalo - Nanang Roswita Paramata; Syamsu Qamar Badu; Novianty Djafri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Literacy is an individual's ability and skills in language i.e. reading, writing, speaking, calculating and problem solving at a certain level of expertise required in daily life. Bullying is as unwanted aggressive behaviour of another young person or group of young people who are not siblings or current dating partners involving an observed or perceived imbalance of power and repeated several times or very likely to be repeated. To prevent bullying, efforts are made to conduct reading and writing literacy activities. The purpose of this study is to see how often students of the Faculty of Medicine, Gorontalo State University do literacy reading and writing, especially about bullying. This study uses a qualitative method, namely an observational survey conducted on the management of the Student Executive Board of the Faculty of Medicine, Gorontalo State University. The results obtained from 15 respondents who were interviewed found that all respondents knew about bullying. Only 2 people have never read about bullying, while 13 have. Writing literacy there are only 2 people who have done about bullying and 13 others never. From the results of the research conducted, it was concluded that all respondents knew about bullying, most had done reading literacy about bullying, and only a small proportion had done writing literacy about bullying.